A merton-model approach to assessing the default risk of Malaysia Public companies - Teo, Tai Wang (Universiti Malaysia Sarawak, (UNIMAS), 2013)
In finance, investment is putting money into something with the expectation to gain either by appreciation in value or a constant cash flow stream generated from that asset, usually over a longer period. Investments come in verities of form, ranking from holding tangible asset like properties to intangible asset like financial instrument such as security or debts. All form of investments involves some from of risk such as investment in equities, property, and even fixed interest securities which are subject to inflation risk.